Persuasion strategies and sexual solicitations and interactions in online sexual grooming of adolescents: Modeling direct and indirect pathways. (13th December 2017) - Gámez‐Guadix, Manuel; Almendros, Carmen; Calvete, Esther; De Santisteban, Patricia
ABSTRACT: Online sexual grooming and exploitation of adolescents is receiving increasing social attention. Drawing on a social influence framework, the aim of this study was to test a model of the direct and mediated relationships between an adult's use of persuasion strategies and online sexual grooming of early adolescents. The initial sample of the study consisted of 2731 early Spanish adolescents between 12 and 15 years old (50.6% female). Of these, 196 adolescents (7.17% of the total; 53% girls) were involved in online grooming (mean age = 14.93, SD = 0.90). Persuasion strategies by the adult through internet increased the probability of using deceit, bribery, and the minor's nonsexual involvement. In addition, deceit and bribery were associated with higher rates of sexual solicitation, which in turn increased abusive sexual interactions. Understanding strategies used by adults to groom minors contributes to the prevention of and intervention in this crucial societal problem.